Prediction method of S-wave velocities in tight sandstone reservoirs – a case study of CO2 geological storage area in Ordos Basin - Li Lin; Wang Haofan; Ma Jinfeng (Open Geosciences)
S-wave velocity, among the critical parameters essential for developing 3D/4D seismic forward models, is prominent. Variations in both P- and S-wave velocities result from changes in the formation pressure and fluid saturation inside reservoirs during CO2 geological storage operations. This study, understanding the significant variety and uneven stress distributions of tight sandstone reservoirs in the Ordos Basin, begins with developing a predictive model for S-wave velocities. The model integrates the Digby and DEM models and takes into account the changes in the formation pressure and alterations in pore shapes. Data from petrophysical experiments are used to validate this model. By comparing the shear wave velocity prediction results under four pore shapes, spherical, needle-shaped, disc-shaped, and coin-shaped gaps, the dominant pore shape of this sedimentary facies belt was selected, and the pore shape of the target layer was identified as needle-shaped pores. The shear wave velocity prediction model for this area was then optimized. Moreover, by analyzing actual well logging data, the methodology is validated and it shows high accuracy when using the dominant pore shapes to predict the S-wave velocity. This study emphasizes how important it is to take geological factors into account when developing 3D/4D seismic petrophysical predication models of S-wave velocities specifically designed for tight sandstone reservoirs.